O setor sucroalcooleiro e o meio ambiente em Quirinópolis-GO: perspectiva jurídico-socioeconômica, 2004-2022. - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Abstract The study explored the evolution of the sugar-alcohol sector in Quirinópolis, Goiás, and its interactions with the environment and legislation. The research was relevant for understanding the economic and environmental dynamics of the sugarcane industry and its impacts on the region. It aimed to address the problem: how was the evolution of the sugar-alcohol sector, from its historical origins to its contemporary expansion in Goiás and specifically in Quirinópolis-GO, influenced by incentive policies and legislation, and what were the consequences of these policies for economic development, environmental aspects, and legal and socioeconomic challenges in the region? The general objective of this research was to analyze the historical conditions that enabled the development of the sugar-alcohol sector in Brazil, in Goiás, and its advancement to the Quirinópolis-GO region, by examining the legislation that ensured incentive policies influencing the sector’s growth and its socio-environmental implications through the analysis of two judicial cases. Specific objectives included: investigating the historical process of sugarcane expansion in Brazil, from colonial times with the first engenhos to the consolidation of the modern sugar-alcohol industry; analyzing Brazilian legislation that ensured modernization incentives and the development of the sugarcane agroindustry in Brazil, Goiás, and Quirinópolis-GO; examining the evelopment of the sugar-alcohol sector in the municipality of Quirinópolis-GO, considering legal, economic, and social aspects, as well as municipal incentives and their impacts on land use; and discussing two judicial cases involving the sugar-alcohol sector, analyzing interactions between law, environment, and society, with the intention of identifying possible socio-environmental impacts, challenges, and legal implications. The study’s methodology was qualitative and descriptive, employing a historical-legal approach to analyze historical documents, legislation, and specialized literature. The study was interdisciplinary, encompassing issues of law and history. The work began with an analysis of the historical process of sugarcane expansion in Brazil, which went through three distinct phases: the colonial engenhos era, the sugar mills, and the modern sugar-alcohol industry. During the engenhos phase, production was based on rudimentary units with slave labor. With the transition to mills, there was a significant advance in efficiency and technology. The final phase, that of the sugar-alcohol industry, was marked by mechanization and diversification of production. Regarding legislation and incentive policies, the study highlighted how national and state legislation, especially in Goiás, favored the growth of the sugar-alcohol sector but often prioritized economic rationality over environmental protection. Incentive policies contributed to the expansion of the sugarcane agroindustry but also revealed gaps in integrating sustainable practices and environmental protection. In Quirinópolis, the combination of demand for biofuels, favorable climatic conditions, and tax incentives drove the growth of the sugar-alcohol sector. Municipal legislation played a crucial role in this development, providing a favorable environment for agroindustry expansion. However, this accelerated expansion brought challenges such as subsidy dependence and environmental issues. The study also analyzed judicial cases related to the sugar-alcohol sector, focusing on litigation involving environmental and socioeconomic damages. The cases often addressed issues such as burning and contamination of crops, with judicial decisions varying in their responses and implications. Sanctions for companies indicated the need for greater oversight and stricter policies. Among the main conclusions, it was noted that the sector's evolution brought significant economic benefits but also highlighted the need for a more balanced approach between economic growth and environmental protection. Identified gaps included the effectiveness of public policies and the long-term impacts of judicial decisions, suggesting the need for further research to explore sustainable practices and evaluate the effectiveness of regulations and incentives. The research provided a comprehensive analysis of the sugar-alcohol sector in Quirinópolis, highlighting the interactions between economic development, legislation, and the environment, and proposed directions for future research and improvements in public policies.
The sugar and alcohol sector and the environment in Quirinópolis-GO: legal-socioeconomic perspective, 2004-2022.
Keywords: Quirinópolis; Setor Sucroalcooleiro; Legislação Ambiental; Cana-de-Açúcar; Impactos Socioambientais; Políticas de Incentivo - Setor Sucroalcooleiro; Sugarcane Sector; Environmental Legislation; Socio-environmental Impacts; Sugarcane; CIENCIAS BIOLOGICAS::ECOLOGIA; SANEAMENTO AMBIENTAL::LEGISLACAO AMBIENTAL